Clinical and cost utility of an intraoperative endoscopic second look in cholesteatoma surgery. (16th October 2018) - Bennett, Marc; Wanna, George; Francis, David; Murfee, Jack; O'Connell, Brendan; Haynes, David
Abstract : Objective/Hypothesis: This study aimed to determine the clinical and cost‐effectiveness of endoscopes during cholesteatoma surgery. More specifically, this study hypothesized that endoscope use would reduce cholesteatoma recurrence rates and cost. Study Design: Case series involving the prospective enrollment of 110 consecutive cholesteatoma patients over a 2‐year period. Methods: Patients underwent cholesteatoma surgery with microscopy. During dissection, the location of the cholesteatoma was assessed. At the end of dissection and before reconstruction, the same subunits were visualized with straight and angled endoscopes for residual cholesteatoma. Hearing was analyzed before surgery and at the last possible examination. Costs were analyzed using Medicare reimbursement rates from the Centers for Medicare and Medicaid Services. Results: Intraoperative endoscopic surveillance was able to detect residual cholesteatoma in 18 patients. With a 0° endoscope, residual cholesteatoma was noted in the epitympanum (two patients), sinus tympani (one patient), and the supratubal air cells (one patient). With a 45° endoscope, residual cholesteatoma was noted in the epitympanum (three patients), sinus tympani (nine patients), the supratubal air cells (two patients), and the mesotympanum (two patients). From a cost analysis, endoscopic surveillance (6110.36 per patient) are less expensive than second look surgeries (11, 829.83 per patient), observation (7097.20 per patient), and observation with annual magnetic resonance imaging studies (9891.95 per patient). The patients hearing improved after surgery, consistent with previous studies. No complications were noted from the use of endoscopes. Conclusions: Intraoperative endoscopic surveillance reduced recurrence in our series of 110 patients. Endoscopes are particularly useful in evaluating the epitympanum, mesotympanum, sinus tympani, and supratubal air cells. Moreover, endoscopic surveillance is cost‐effective. Level of Evidence: 4 Laryngoscope, 128:2867–2871, 2018